Liver knockout of MCU leads to greater dysregulation of lipid metabolism in MAFLD - Qichao Liao; Yurou Zhang; Tingli Pan; Yu Sun; Siqi Liu; Zhiwang Zhang; Yixing Li; Lin Yu; Zupeng Luo; Yang Xiao; Xinyi Qi; Tianyu Jiang; et al. (Scientific Reports, 2024)
Abstract Metabolic-associated fatty liver disease (MAFLD) is a common chronic condition that poses a significant threat to human health. Mitochondrial dysfunction, particularly involving the mitochondrial Ca2+ uniporter (MCU), plays a key role in its pathogenesis. This study aimed to investigate the impact of the MCU gene on hepatic lipid metabolism in mice fed a high-fat diet. Using MCU knockout and wild-type mice, subjected to either a high-fat or normal diet for 14 weeks, we observed notable Steatosis and liver weight gain in MCU-deficient mice. Liver function markers, serum triglycerides, very low-density lipoprotein (VLDL) levels, and ApoB protein expression were all significantly elevated. Mechanistic studies revealed that MCU deletion led to mitochondrial dysfunction, increased oxidative stress. These findings highlight the critical role of the MCU gene in maintaining hepatic lipid balance and suggest its potential as a therapeutic target for managing nonalcoholic fatty liver disease.